Restructuración técnico administrativa en la empresa Punto Aparte Moda en Tejidos S.A.S. (2018)
The technical-administrative restructuring in the company Punto Aparte Moda in Tejidos SAS, whose main activity is the manufacture of garments except leather garments, starts with a diagnosis of the sector using tools such as the PESTAL and SWOT analysis to identify the relevant aspects in the thread sector (primary material), and the textile-garments sector. With the technical study, all the times of the activities that make up each manufacturing process are standardized and the production capacities, the necessary machinery and human resource requirements are established, the production plan is strengthened, the raw material requirement plan and negotiation strategies are established with the different suppliers that meet a high rating in their most important criteria. In the administrative study, strategic planning is defined and the organizational structure is elaborated, where a salary adjustment is made and the position of human resources is proposed to achieve an appropriate performance and management, both business and industrial.